Eco-Physiological Responses of Dominant Species to Watering in a Natural Grassland Community on the Semi-Arid Loess Plateau of China - Niu, Furong; Duan, Dongping; Chen, Ji; Xiong, Peifeng; Zhang, He; Wang, Zhi; Xu, Bingcheng (Frontiers in Plant Science, 2016)
Altered precipitation regimes significantly affect ecosystem structure and function in arid and semi-arid regions. In order to investigate effects of precipitation changes on natural grassland community in the semi-arid Loess Plateau, the current research examined eco-physiological characteristics of two co-dominant species (i.e., Bothriochloa ischaemum and Lespedeza davurica) and community composition following two watering instances (i.e., precipitation pulses, July and August, 2011, respectively) in a natural grassland community. Results showed that the photosynthetic rate, transpiration rate, stomatal conductance and intercellular CO2 concentration rapidly increased on the first to third day following watering in both species, and both months. Under watering treatments, the maximum net photosynthetic rates appeared on the second to third day after watering, which increased 30−80% in B. ischaemum and 40−50% in L. davurica compared with non-watering treatments, respectively. Leaf water use efficiency kept stable or initially decreased in both species under watering treatments. Watering in July produced more promoting effects on grass photosynthesis than in August, particularly in B. ischaemum. Community above-ground biomass at the end of the growing season increased after watering, although no significant changes in species diversity were observed. Our results indicated that timing and magnitude of watering could significantly affect plant eco-physiological processes, and there were species-specific responses in B. ischaemum and L. davurica. Pulsed watering increased community productivity, while did not significantly alter community composition after one growing season. The outcomes of this study highlight eco-physiological traits in dominant species may playing important roles in reshaping community composition under altered precipitation regimes.